2020
DOI: 10.1186/s12909-020-02128-y
|View full text |Cite
|
Sign up to set email alerts
|

Nursing staff’s and physicians’ acquisition of competences and attitudes to interprofessional education and interprofessional collaboration in pediatrics

Abstract: Background: Interprofessional education (IPE) is deemed essential for interprofessional collaboration (IPC) in healthcare systems. IPC has positive effects for both patients and healthcare professionals. Especially in pediatrics, IPC is paramount for adequate care of patients and their families though there is a lack of data on the attitudes towards IPE and IPC and acquisition of respective competences in pediatric nursing and medical staff. Methods: Frequencies of interactions and attitudes towards IPE and IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
1
6
0
3
Order By: Relevance
“…However, this may differ across professions. In one study in Germany, physicians acquired more interprofessional skills including teamwork through work experience rather than pre-service training, while the converse was true for nurses [14]. Interprofessional training has been shown to improve interprofessional competencies including team skills of practicing health professionals [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…However, this may differ across professions. In one study in Germany, physicians acquired more interprofessional skills including teamwork through work experience rather than pre-service training, while the converse was true for nurses [14]. Interprofessional training has been shown to improve interprofessional competencies including team skills of practicing health professionals [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous studies in the interprofessional field, which have already shown that the relevance of interprofessionalism can be learned in a course [ 57 ]. This is important because the implementation of interprofessional teaching courses for students has so far been inadequate [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Os dados observados em nossos achados corroboram outros estudos 15,16,21,22 , demonstrando que esse problema não ocorre somente com a área de fisioterapia. Por isso, sugerimos algumas soluções para o problema que podem ser vislumbradas: 1) inclusão no curriculum do Curso de Medicina e dos outros cursos da área da saúde de uma disciplina que discuta o papel e as responsabilidades de cada profissional dentro de uma UTI; por meio de discussão do caso com a equipe multidisciplinar, que poderia estreitar a comunicação entre todos os profissionais da equipe; 2) desenvolvimento de palestras aos alunos do Curso de Medicina sobre a atuação das diferentes áreas dentro de um regime multidisciplinar de atuação; 3) desenvolvimento e distribuição de material pedagógico sobre o assunto durante a residência dos médicos; 4) reuniões periódicas entre as equipes de profissionais para melhorar a comunicação, definir limites de atuação, remover dúvidas, estudar casos, trocar conhecimentos; e 5) maior atenção da administração hospitalar, visando à melhora do clima organizacional dentro das equipes multidisciplinaresestas duas últimas já no âmbito da atividade profissional dentro do hospital, nas áreas ambulatorial, enfermaria e UTI.…”
Section: Discussionunclassified